2021
DOI: 10.12998/wjcc.v9.i18.4506
|View full text |Cite
|
Sign up to set email alerts
|

Roles of vitamin A in the regulation of fatty acid synthesis

Abstract: Dietary macronutrients and micronutrients play important roles in human health. On the other hand, the excessive energy derived from food is stored in the form of triacylglycerol. A variety of dietary and hormonal factors affect this process through the regulation of the activities and expression levels of those key player enzymes involved in fatty acid biosynthesis such as acetyl-CoA carboxylase, fatty acid synthase, fatty acid elongases, and desaturases. As a micronutrient, vitamin A is essential for the hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 98 publications
1
7
0
Order By: Relevance
“…In the current study, correlation analyses provided evidence that higher inflammatory parameters, such as C-reactive protein, were significantly associated with reduced plasma VA levels. This finding supported available information showing that reduced plasma levels of VA were often associated with infection and acute inflammatory conditions [ 10 , 12 , 53 , 54 ].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In the current study, correlation analyses provided evidence that higher inflammatory parameters, such as C-reactive protein, were significantly associated with reduced plasma VA levels. This finding supported available information showing that reduced plasma levels of VA were often associated with infection and acute inflammatory conditions [ 10 , 12 , 53 , 54 ].…”
Section: Discussionsupporting
confidence: 90%
“…VA is known to play a very important role in lipid metabolism [ 9 , 10 , 11 ]. The level of VA and its metabolite retinoic acid (RA) regulate the pivotal lipogen-ic enzymes, as well as their gene expressions involved in lipid metabolism [ 12 ]. Epidemiological and mechanism studies have indicated that VA can stimulate lipid catabolism in some tissues and contribute to reducing the incidence of obesity [ 13 ] and the risk of atherosclerotic cardiovascular disease (ASCVD) [ 14 , 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…In obesity, white adipose tissue secretes large amounts of adipokines, including RBP4, which have local and systemic effects (retinol homeostasis and transport) and contribute to IR ( 15 , 32 ). The association between elevated serum levels of RBP4 (analyzed by ELISA) and obesity/T2D was reported by Yang et al ( 26 ) in the Chinese population in obese patients with and without diabetes. However, no significant association was noted between non-diabetic and diabetic groups, suggesting that hyperglycemia was not associated with elevated serum RBP4 levels ( 33 ).…”
Section: Rbp4 In Obesitymentioning
confidence: 53%
“…To accomplish this, it must be converted to retinaldehyde by the enzyme retinol dehydrogenase 10. Subsequently, retinaldehyde is oxidized to RA by retinaldehyde dehydrogenases 1–3 ( 26 28 ). RA activates or suppresses gene transcription via nuclear receptors, namely retinoic acid receptor (RAR)α, RARβ and RARγ ( 28 , 29 ).…”
Section: Rbp4mentioning
confidence: 99%
“…Studies have shown that vitamin A plays a role in regulating glucose and fatty acid metabolism. RA regulates the expression level of the enzymes involved in fatty acid synthesis [ 49 ], while fatty acids and retinoids control the lipid metabolism by activating the peroxisome proliferator-activated receptor (PPAR)-RXR dimer [ 50 ]. Shijin Yin et al [ 51 ] found that high retinoid concentrations trigger sensory hypersensitivity through the activation of TRPV1 receptors, while oral or intrathecal administration of all-trans retinoic acid (ATRA) can induce nociceptive behaviors in rodents [ 52 ].…”
Section: Discussionmentioning
confidence: 99%